Sylwetki procesualistów - Budniak-Rogala, Aleksandra; Pyrz, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
This study aims at bringing the profiles of employees, who were hired in the Department of Civil Procedure in the years 1945–2015, closer to the readers. On account of large period, whichrelates to the article, its authors decided to introduce only those, who were or still are hired in the mentioned institution and received at least a doctoral degree in legal science. This kind of categorization is an optimal solution, which allows to present development of civil proceedings in the discussed period at the University of Wrocław.
Keywords: Zakład Postępowania Cywilnego; Wydział Prawa Administracji Ekonomii UWr; sylwetki profesorów; historia